Experimental aversion therapy for stuttering - Vishwanath NS (Journal of All India Institute of Speech and Hearing, 1971)
Of recent, great interest has been shown in the application of aversive stimulus contingent on stuttering blocks as a therapeutic strategy (Goldiamond 1 965; Martin and Siegal 1966a; Martin and Siegal 1966 b). The assumption underlying these efforts are that stuttering blocks are subject to the control of the law of effect, hence an aversive stimulus would decrease the probability of their occurrence.